Dry matter dynamics and carbon flux along riverine forests of Gori valley, Western Himalaya - Bisht, Soni; Bargali, Surendra Singh; Bargali, Kiran; Rawat, Yashwant Singh; Rawat, Gopal Singh (Frontiers in Forests and Global Change, 2023)
Introduction Riverine forests in the Himalaya represent a biodiverse, dynamic, and complex ecosystem that offers numerous ecosystem services to local and downstream communities and also contributes to the regional carbon cycle. However, these forests have not been assessed for their contribution to dry matter dynamics and carbon flux. We studied these parameters along three classes of riverine forests in eastern Uttarakhand, dominated by Macaranga, Alnus, and Quercus-Machilus forest. Methods Using volume equations, we assessed tree biomass, carbon storage, and sequestration in the study area. Results The total standing tree biomass in Macaranga, Alnus, and Quercus-Machilus forest ranged from 256.6 to 558.1 Mg ha−1, 460.7 to 485.8 Mg ha−1, and 508.6 to 692.1 Mg ha−1, respectively. A total of 77.6–79.6% of vegetation biomass was stored in the aboveground biomass and 20.4–22.4% in belowground plant parts across the riverine forests. The carbon stock in Macaranga forest ranged from 115.5 to 251.1 Mg ha−1, in Alnus forest from 207.3 to 218.6 Mg ha−1, and in Quercus-Machilus forest from 228.9 to 311.4 Mg ha−1. The mean annual litterfall was accounted maximum for Quercus-Machilus forest (5.94 ± 0.54 Mg ha−1 yr.−1), followed by Alnus (5.57 ± 0.31 Mg ha−1 yr.−1) and Macaranga forest (4.67 ± 0.39 Mg ha−1 yr.−1). The highest value of litterfall was recorded during summer (3.40 ± 0.01 Mg ha−1 yr.−1) and the lowest in winter (0.74 ± 0.01 Mg ha−1 yr.−1). The mean value of net primary productivity and carbon sequestration was estimated to be highest in Quercus-Machilus forest (15.8 ± 0.9 Mg ha−1 yr.−1 and 7.1 ± 0.9 Mg C ha−1 yr.−1, respectively) and lowest in Alnus forest (13.9 ± 0.3 Mg ha−1 yr.−1 and 6.1 ± 0.3 Mg C ha−1 yr.−1, respectively). Discussion The results highlight that riverine forests play a critical role in providing a large sink for atmospheric CO2. To improve sustainable ecosystem services and climate change mitigation, riverine forests must be effectively managed and conserved in the region.